Polycystic Ovarian Syndrome (PCOS): A Growing Health Concern - Roy, Gobinda Chandra; Samsad, Gulafshan; Chatterjee, Rupayan; Dutta, Sumana (American Journal of Bioscience and Clinical Integrity, 2025)
Polycystic ovarian syndrome (PCOS) is a condition characterized by irregular menstrual cycles due to the lack of regular ovulation and elevated levels of androgens (male hormones). It is an important cause of female infertility and a precursor to other serious conditions such as obesity, cardiovascular diseases, type 2 diabetes, and endometrial cancer. The diagnosis of PCOS is tough during the first two years following menarche because normal pubertal changes can mimic symptoms of PCOS. These symptoms are an ovulatory infertility, irregular menstrual cycles, increased androgen effects, transient multi-follicular ovarian morphology, and relative insulin resistance. Women who have PCOS are at high risk for several serious complications, some of which can be life-threatening complications. Common clinical features of PCOS include irregular or heavy or no menstrual periods, acne, excess facial and body hair, difficulty in getting pregnant and patches of thick, darker, velvety skin, pain in the pelvis. The diagnosis of PCOS is based on the presence of any two of the following three criteria, no ovulation, high androgen levels, and ovarian cysts. Lifestyle modifications such as regular exercise and weight reduction may improve the situation. Birth control pills can help to regulate menstrual periods, reduce excess hair growth, and improve acne. Weight loss, metformin, or clomiphene also helps to improve fertility. Early diagnosis and treatment of the disease help to reduce the risk of many of the complications. This review briefly pronounces the major causes of PCOS and effective control strategies.